Divergent Trajectory of Soil Autotrophic and Heterotrophic Respiration upon Permafrost Thaw - Wang, Guanqin; Chen, Leiyi; Zhang, Dianye; Qin, Shuqi; Peng, Yunfeng; Yang, Guibiao; Wang, Jun; Yu, Jianchun; Wei, Bin; Liu, Yang; Li, Qinlu; Kang, Luyao; et al. (Environmental Science & Technology, 2022)
Warming-induced permafrost thaw may stimulate soil respiration (Rs) and thus cause a positive feedback to climate warming. However, due to the limited in situ observations, it remains unclear about how Rs and its autotrophic (Ra) and heterotrophic (Rh) components change upon permafrost thaw. Here we monitored variations in Rs and its components along a permafrost thaw sequence on the Tibetan Plateau, and explored the potential linkage of Rs components (i.e., Ra and Rh) with biotic (e.g., plant functional traits and soil microbial diversity) and abiotic factors (e.g., substrate quality). We found that Ra and Rh exhibited divergent responses to permafrost collapse: Ra increased with the time of thawing, while Rh exhibited a hump-shaped pattern along the thaw sequence. We also observed different drivers of thaw-induced changes in the ratios of Ra:Rs and Rh:Rs. Except for soil water status, plant community structure, diversity, and root properties explained the variation in Ra:Rs ratio, soil substrate quality and microbial diversity were key factors associated with the dynamics of Rh:Rs ratio. Overall, these findings demonstrate divergent patterns and drivers of Rs components as permafrost thaw prolongs, which call for considerations in Earth system models for better forecasting permafrost carbon-climate feedback.